Galen Medical Journal (GMJ) Title Readability Index: - Khodabakhshi, Morteza; Borhani Haghighi, Afshin (Galen Medical Journal, 2015)
Background: Title choice will undoubtedly pave the way for the informed readership to either devour a text or just spurn it. Therefore, authors are duly required to have a deep understanding of titling trends and potential inferences to be drawn by their addressees. As a case in point, choosing proper titles for medical articles is a subject of much debate among researchers to such an extent that it is postponed to be written till the finalization of a given manuscript. Titles form expectations, preconceptions, presuppositions and most importantly judgment on reader’s side. Quality highly-cited research papers submitted to the internationally renowned Galen Medical Journal (GMJ) as a true index of Iranian medical journalism covering varied areas of research in both medical and interdisciplinary fields concerning health-related topics, provide a performance benchmark to firstly evaluate titling trends among Iranian authors, secondly to improve writing strategies and finally to meet international standards. Materials and Methods: To conduct this meta-analysis, researchers collected all articles published by GMJ. 100 titles were randomly chosen to be linguistically analyzed by Advanced Text Analyzer software. All data were fed into MC-Excel to recognize any distributional regularity in titling, subconsciously followed by GMJ authors. Results: The meta-analysis of randomly chosen article titles revealed a well-established trend in high Lexical Density standing above 76.67 for all titles indicating author’s frozen style and academic register in their manuscripts. Moreover, Title Length hits 14.34 on average signifying author’s inclination for longer titles. It might negatively impact the whole discourse due to heavy cognitive load. Gunning Fog Index ranging averagely 16.94 estimates at least 17 years of formal education needed to understand a text on first reading with no difficulty. Additionally, introducing poly-morphemic lexical items into author’s title in nearly all cases, owing to their mental load, augments text difficulty. Conclusion: Authors of medical articles can increase their article’s readability through their acquaintance with text mechanics such as lexical density, Gunning Fog Index and Readability criteria. Authors are strongly recommended to shorten title length, introduce fewer poly-morphemic words and utilize highly frequent mono-morphemic lexical items in order to increase article readability. [GMJ. 2015;4(3):100-3]